'Those who cannot remember the past are condemned to repeat it': Drug-susceptibility testing for bedaquiline and delamanid. (March 2019) - Köser, Claudio U.; Maurer, Florian P.; Kranzer, Katharina
Highlights: Breakpoints that define susceptibility and resistance to anti-tuberculosis drugs are crucial for optimal treatment. Breakpoints needs to be based on modern microbiological principles taking into account clinical outcome data. Robust breakpoints still do not exist for bedaquiline and delamanid and are urgently needed. Abstract: Despite being fundamental to all treatment decisions, the breakpoints that define susceptibility and resistance to conventional anti-tuberculosis (TB) drugs were traditionally defined based on expert opinion as opposed to modern microbiological principles. As a result, the breakpoints for several key drugs (i.e. amikacin, levofloxacin, and moxifloxacin) were too high, resulting in the systematic misclassification of a proportion of resistant strains as susceptible. Moreover, a recent systematic review of clinical outcome data prompted the World Health Organization (WHO) to make significant changes to its treatment guidelines. For example, capreomycin and kanamycin are no longer recommended for TB treatment because their use correlates with worse clinical outcomes. This history notwithstanding, robust breakpoints still do not exist for bedaquiline and delamanid six years after their approval. This was compounded by the fact that access to both agents for drug-susceptibility testing had initially been restricted. It is incumbent upon the European Medicines Agency, the United States Food and Drug Administration, and WHO to ensure that drug developers generate the necessary data to set breakpoints as a prerequisite for the approval of new agents.